The Differences In Perceptions of Social Support And Self-Esteem of Caregivers for People With Mental Disorders Based on Gender and Age - Rahayu, Rita; Budiarto, Eka; Tukimin, Tukimin; Kusuma, Nur Intan (Jurnal Kesehatan - STIKes Prima Nusantara, 2024)
Background: A caregiver's ability to care for patient with mental disorders is determined, in part, by perceptions of social support and self-esteem. Apart from that, caregiver characteristics can also determine perceptions of social support and self-esteem.Objective: This study aims to determine differences in perceptions of social support and self-esteem of PMD caregivers based on gender and occupation with age covariates of PMD caregivers.Method: This research was a correlative descriptive study with a cross sectional approach with the sample being caregivers of patient with mental disorders. The research was conducted in Pekalongan regency with a sampling technique using purposive sampling. The sample size was 101 respondents. Data was obtained using a characteristics questionnaire, the Multidimensional Perceived Social Support questionnaire, and the Rosenberg Self-Esteem Scale. Data were analyzed using multiple analysis of covariance.Result: A total of 77.2% of caregivers were women with an average caregiver age of 45.5 years in the age range 18-59 years. The average perceived social support was 73.59 in the score range 61-82 and the average self-esteem was 35.14 in the score range 29-40. There is a significant difference in perceptions of social support and caregiver self-esteem based on gender after controlling for age (p value 0.037). The results of the post hoc test showed that differences in gender caused significant differences in the self-esteem of caregivers of patient with mental disorders (F (1,97) = 4.411; P = 0.038; Alpha = 0.05).Conclusion: There were significant differences in perceptions of social support and self-esteem of PMD caregivers based on sex and occupation after age-controlled with age. Efforts to increase perceptions of social support and self-esteem can be focused by paying attention to gender and age factors.